2019
DOI: 10.1016/j.jss.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Fluorescence and Near-Infrared Spectroscopy in Detection of Colorectal Cancer

Abstract: Magnetic resonance spectroscopy a b s t r a c tBackground: Colorectal cancer is one of the most common malignancies worldwide. There is an urgent need for simple and fast methods to improve tumor detection in the diagnostic and intraoperative setting to avoid complications and provide objective information in distinguishing malignant and benign colorectal tissue. Optical spectroscopy methods have recently shown a great potential for this discrimination in different organs. Materials and methods:In this pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
(33 reference statements)
0
21
1
1
Order By: Relevance
“…As expected, the closest classification performance compared to the present study was the SVM classifier. Still, Ehlen et al 48 found 6.1% higher sensitivity, 20% lower specificity and 5.4% lower accuracy compared to the present study, which may be originated by using 400-µm fiber SDD and substantially smaller sample size (number of patients and spectra).…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…As expected, the closest classification performance compared to the present study was the SVM classifier. Still, Ehlen et al 48 found 6.1% higher sensitivity, 20% lower specificity and 5.4% lower accuracy compared to the present study, which may be originated by using 400-µm fiber SDD and substantially smaller sample size (number of patients and spectra).…”
Section: Discussioncontrasting
confidence: 82%
“…Usefulness of the extended wavelength range. Based on the classification performance on the wavelength ranges of previous studies [39][40][41][42][43][44][45][46][47][48][49][50] , we analyzed the potential benefit of using the extended wavelength for colorectal cancer (CRC) detection. In order to be consistent with the findings of previous studies, this analysis consisted of the comparison of the sensitivity, specificity, accuracy and AUC using the small SDD probe (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations